Structural studies of FXII and associated proteins - Brown, Alexander (2023)
Blood coagulation factor XII and proteins such as Von Willebrand factor that it interacts with are key parts of the intrinsic coagulation system and mediate the physiological response to damage. This work investigates the mechanisms of FXII and VWF function. Current anti-coagulation treatments can have severe side effects due to off-target effects caused by limited target specificity, resulting in a lack of clotting even when desirable. Targeting individual coagulation proteins such as FXII may produce more precise treatments that are both more effective and have fewer side effects. As part of the pathway of identifying novel small molecule anticoagulants for FXII, this work examined the binding modality of a small library of FXII inhibiting compounds created using results from an unpublished high throughput activity assay at the University of Nottingham. These compounds were subjected to complementary high-throughput virtual screening using GLIDE, combined with individual high-flexibility in-silico binding experiments and revealed a novel structure-function relationship including specificity involving the S1’ pocket of FXII and proposal of a slow forming covalent mechanism with the active site Serine 195. Four constructs of FXII were successfully purified including higher-yielding mouse variants of both the full-length protein and the heavy chain only. The FXII binding protein gC1qR was also produced successfully, and alongside commercial proteins, experiments were performed to characterise FXII binding. A recent unpublished crystallography structure of the FXII heavy chain suggested a feasible conformation of a dimeric FXII, which has not been seen before. This work explores this hypothesis and identifies three anionic polymers which appear to cause FXII to multimerise - polyacrylic acid, heparin and polyphosphate. Micro-scale size exclusion chromatography experiments show a polymer-length dependant multimerisation of FXII. FXII binds to a large variety of proteins which are essential for its function, including Von Willebrand factor, of which the A1 domain has been recently identified as the determinant of FXII binding. A 2.1Å structure was solved using crystallography of this A1 domain bound to the first approved nanobody therapy – Caplacizumab. Information from this structure has shown that the terminal regions of the A1 are responsible for its shear force-dependant activation and that limiting the movement of those regions is the mechanism for the nanobody therapy.